EUROPEAN CONTEXT CHINESE MENSWEAR DESIGNERS’ CREATIVITY - ЛАГОДА, О. М.; Лінь, Я. (Art and Design, 2023)
The purpose of the study is to analyze the history of the influence of European fashion on the development of design practices in China; to investigate how the work of Chinese menswear designers shows signs of "Europeanness", which global fashion trends are supported by Chinese men and in what directions they are developing. Methodology. The study uses cultural and historical analysis to identify the peculiarities of men’s fashion in China and its development; comparative historical and typological methods to characterize individual samples of clothing and changes in contemporary design; a method of stylistic description of interpretations of men’s costume in the work of individual designers and brands; iconographic analysis of visual sources to establish the influence of European trends in men’s fashion on contemporary design practices. Results. The degree of study of the topic in the scientific and professional literature is determined; the sources that outline the historical development of men’s fashion in China during the twentieth - early twenty-first centuries are analyzed. The main approaches to the design of men’s clothing that have developed historically are indicated; trends in the development of modern design practices for men’s clothing in China and in the work of Chinese designers outside the country - in Europe; typical and innovative approaches in their work, features that were formed under the influence of European culture and in synthesis with the traditions of Chinese culture are outlined. The scientific novelty of the study lies in a comprehensive consideration of the "Europeanness" of men’s fashion in China as one of its most characteristic features that has developed historically. The influence of European culture and a strong commitment to their own national traditions have synthesized a special style in the work of contemporary Chinese menswear designers, which today influences world fashion in general. Practical significance. The materials of the article can be used in the educational process in the training of specialists in fashion design, stylists, and in writing scientific papers.